Caffeine administration alters the behaviour and development of Galleria mellonella larvae - Maguire, Ronan; Kunc, Martin; Hyrsl, Pavel; Kavanagh, Kevin (Neurotoxicology and teratology, 2017)
The effect of feeding caffeine on the behaviour and neural proteome of Galleria mellonella larvae was assessed. Caffeine was administered to larvae by force feeding and the metabolites theobromine and theophylline were subsequently detected by RP-HPLC analysis. Administration of caffeine to larvae resulted in reduced movement and a reduction in the formation of pupae. The production of the muscle relaxant theophylline may contribute to the reduction in larval movement. Analysis of the changes in proteome of the brain and surrounding tissues of caffeine fed larvae revealed an increase in the abundance of immune related proteins such as immune-related Hdd1 (6.28 fold increase) and hemolin (1.68 fold increase), ATPase associated proteins such as H+ transporting ATP synthase O subunit isoform 1 (1.87 fold increase) and H+ transporting ATP synthase delta subunit (1.53 fold increase) and proteins indicative of brain trauma such as troponin T transcript variant B, partial (1.55 fold increase). Proteins involved in development and protein degradation such as SUMO-activating enzyme subunit 1 (3.08 fold decrease) and chitin deacetylase, partial (3.67 fold decrease) were decreased in abundance. The results presented here indicate that caffeine is metabolised in a similar way in G. mellonella larvae to that in mammals and results in a variety of behavioural and developmental alterations. Utilisation of insects for studying the effects of caffeine and other neuroactive compounds may offer new insights into their mode of action and reduce the need to use mammals for this type of analysis.
Keywords: hmyzí proteiny; larva; Moths; Mini-model; In vivo screening; Immunity; chování zvířat; Insect Proteins; Central Nervous System Stimulants; stimulanty centrálního nervového systému; Movement; Proteome; proteom; zvířata; pohyb; můry; Animals; Larva; mozek; Brain; kofein; Galleria; Caffeine; Behavior, Animal